Process evaluation of a mobile phone-based intervention to support post-abortion contraception in Cambodia - Chris Smith; Sokhey Ly; Vannak Uk; Ruby Warnock; Phil Edwards; Caroline Free (BMC, 2017)
Abstract Background The MObile Technology for Improved Family Planning (MOTIF) trial assessed a mobile phone-based intervention comprising voice messages and counsellor support to increase post-abortion contraception at four Marie Stopes International clinics in Cambodia. The aim of this process evaluation was to assess participants' interaction with the intervention from a service provider perspective. Methods (1) We conducted a descriptive analysis to assess participants' interaction with the intervention. (2) In order to explore how the intervention might work, we assessed associations between interaction with the intervention and contraception use using logistic regression analysis. (3) We undertook a logistic regression analysis to assess associations between baseline socio-demographic factors and ever requesting to speak to a counsellor (pressing '1'), a variable found to be associated with contraception use. Results Amongst 249 women that received six interactive voice messages +/− counsellor support for contraception, around half actively requested to speak to a counsellor (pressed '1') and over 90% spoke to a counsellor at some stage. Women who spoke to the counsellor having requested to (by pressing '1') were more than four times as likely to be using effective contraception at four months compared to women who didn't request or speak to the counsellor (Odds Ratio 4.39; 95% CI: 1.15-16.71). There was a small, non-statistically significant increase in contraception use amongst women that spoke to the counsellor without requesting a call. Increased parity, a history of >2 previous induced abortions, lower socio-economic status, and medical abortion (after adjusting for age, socio-economic status and residence) were associated with requesting to speak to a counsellor. Conclusions The interactive message can identify a subgroup of women in whom counselling will be more effective and appears to be equitable in terms of engaging those most in-need. The intervention could be adapted based on the findings of this study.